The Decisions to Open a Relationship: To Three or Not to Three - Beggan, James K. (Lexington Books, 2023)
The unique contribution of The Decisions to Open a Relationship: To Three or Not to Three is how James K. Beggan considers the social and psychological processes involved in how someone makes the decision to transition from a monogamous to a consensually nonmonogamous relationship. Informed by extensive research drawn from sociology, psychology, and the decision-making literature, Beggan provides a comprehensive analysis of processes associated with expressing the desire to open a previously closed romantic relationship, with special emphasis on the unique dynamics of the triad. His analysis provides valuable insights into managing jealousy, maintaining trust, and establishing healthy boundaries. He examines moral issues associated with breaking the promise of a monogamous relationship to satisfy goals related to personal growth. The book addresses issues related to intersectionality that involve sexual orientation, gender identity, and race.